The Incidence of Neonatory Jaundice Reviewed From Low Birth Weight And Gestational Age In The Kenanga Room Of Kuala Pembuang Hospital - Asriyana Ilmiyanti; Miftakhur Rohmah; Riza Tsalatsatul Mufida; Shanty Natalia (Journal of Health Science Community, 2025)
More than 50% of newborns experience hyperbilirubinemia, both in full-term and premature babies. Jaundice is one of the contributors to infant morbidity in Indonesia with several causative factors that often occur, including gestational age and low birth weight (LBW). The purpose of this study was to analyze the relationship between infant birth weight and gestational age with the incidence of neonatal jaundice at Kuala Pembuang Regional Hospital . Research This use method study descriptive with approach cross sectional, sample study as many as 44 respondents, used Total sampling technique, Research instrument using Record data medical. Data analysis in the test use test statistics chi-square. Chi square test results on variable heavy body born to jaundice neonatum obtained results p-value of 0.0000 > α = 0.05 and variable age pregnancy to jaundice neonatorum obtained results p-value of 0.0001 > α = 0.05 so that can concluded that there is connection heavy body born low And age pregnancy to incident jaundice neonatorum in the room Remember Kuala Pembuang Regional Hospital. Part of it big Respondent No experience jaundice neonatorum as many as 33 (75%). Some big Respondent experience heavy body normal birth (BBLN) as many as 31 (70.5%). Most of them big Respondent as many as 33 (75%) with age pregnancy aterm.